Cytohistopathological and immunohistochemical correlation of soft tissue tumors - Chandralekha, J.; Lakshmi, A. Bhagya; Bharathi, I. Vijaya; Rajagopal, Metta (International Journal of Research in Medical Sciences, 2017)
Background: Fine needle aspiration cytology has become an established tool in the diagnostic armamentarium of many clinical practices. The initial diagnosis of many mass lesions, both superficial and deep-seated, can often be readily and safely assessed by fine needle aspiration cytology. In our study, we assessed 361 cases of soft tissue tumors by fine needle aspiration cytology during a period of three years. We tried to follow up as many cases as possible to obtain corresponding excision biopsies for histopathological examination. Immunohistochemical studies were also performed on biopsy sections in some cases for confirmation of diagnoses. Aims and objectives: 1) To study the age, sex and site-wise distribution of soft tissue tumors. 2) To assess the utility of fine needle aspiration cytology in diagnosing various types of soft tissue tumors. 3) To assess the sensitivity, specificity, positive and negative predictive values, and overall histological correlation percentage of fine needle aspiration cytology in diagnosing soft tissue tumors. Methods: Aspirations were carried out using a 22 gauge disposable needle and a 10c.c disposable syringe for suction. Wet-fixed smears were stained with hematoxylin and eosin and pap stain. Dry-fixed smears were stained with May-Grunwald Giemsa stain. Periodic Acid Schiff stain was used in some cases of extraskeletal Ewing’s sarcoma. Corresponding biopsy sections were stained with hematoxylin and eosin. Immunohistochemical stains were also used in some of the cases for confirmation of diagnosis. Results: Of the 361 cases recorded in our study, 320 patients could be successfully followed up and excision biopsies were obtained. The remaining 41 patients were excluded from the study due to inability to obtain biopsy. Of the 320 cases, 200 were diagnosed as benign soft tissue tumors, while 120 were diagnosed as malignant on cytological examination. The median age of occurrence of benign soft tissue tumors was 34.23years, while that of malignant soft tissue tumors was 48.33years. Prevalence was highest in the age group of 20-49years, during which majority were benign lesions. Soft tissue tumors were more common in the lower extremities with predominant benign tumors, while malignant tumors were more common in the trunk. Sexwise distribution showed a male:female ratio of 1.76:1. Various patterns were observed in cytology. The commonest tumors were lipomas (55%), followed by benign peripheral nerve sheath tumors (37%). Malignant soft tissue tumors constituted 37.5% cases, among which malignant fibrous histiocytoma was the most frequent tumor. Soft tissue sarcomas were classified into 5 general categories on the basis of predominant appearance in aspiration smears: I. Myxoid II. Spindle cell III. Pleomorphic IV. Polygonal V. Round cell. Immunohistochemical studies were done for some tumors with vimentin, desmin, S-100 protein and Neuron Specific Enolase (NSE), Leucocyte Common Antigen (LCA), cytokeratin (CK) and Epithelial Membrane Antigen (EMA). A comparative analysis was done between the cytology report and histopathology. Conclusion: Final evaluation of the results showed that the diagnostic accuracy of fine needle aspiration cytology in soft tissue tumors was 96.88%, sensitivity was 95.08% and specificity was 97.98%.Thus our study proves the efficacy of fine needle aspiration cytology in the diagnosis of soft tissue tumors as a useful cost-effective procedure.